Dramaturgy of Women's Leadership Using Facebook Social Media (Case Study: Independent Prosperous Women's Cooperative in Cilegon City, Banten Province) - Laura Irawati; Alfred Inkiriwang; Larasati Simatupang; Marisi Pakpahan (JURNAL ABDIMAS MADUMA, 2025)
This study explores the dramaturgy of women’s leadership through the use of Facebook as a communication and leadership strategy platform. Focusing on the Independent Prosperous Women's Cooperative in Cilegon City, Banten Province, it examines how female leaders manage impressions and build public images via digital media. Using the ACTORS Theory as an analytical framework, the research applies a dramaturgical approach to analyze how leaders present themselves both in the "front stage" (public interactions) and "back stage" (internal strategy and decision-making).This qualitative case study employs in-depth interviews, observation, and content analysis of Facebook posts. Findings reveal that Facebook enhances the leadership role of women, particularly those facing limitations in fully performing their duties offline. Social media becomes a vital tool for maintaining stakeholder communication and increasing organizational visibility. The study shows that successful impression management on Facebook—aligned with the ACTORS indicators—contributes to cooperative success. The research concludes that Facebook offers strategic opportunities for female leaders to construct and display their leadership roles effectively. However, further studies are recommended to explore women’s dramaturgical leadership on other social platforms like Instagram and TikTok. Keywords: Dramaturgy; Women's Leadership; Cooperative; Facebook